THE DESIGN OF THE FUZZY SYSTEMS IN SELECTING THE STUDENTS’ CONCENTRATION IN TERMS OF DETERMINING THE TOPIC OF THE THESIS - Yulmaini Yulmaini; Lia Indriyati (Prosiding International conference on Information Technology and Business (ICITB), 2016)
The Graduate Program of Information Technology Department of IBI Darmajaya has some concentrations. They are Software Engineering and Information Systems. During this time, the decision made by the students to choose the topic of their thesis is based on their interest on the providedconcentration, not based on theirexpertise.Beside the scores of the course that the students take, there are other factors that influence in selecting the concentration. They are interest and motivation possessed by the students. These factors can early help the students develop the skills that they have so that they can be more focus on developing capabilities. The objective of this research was to produce a design ofthe fuzzy systemswhich could help the students in determining the concentration and the topic of the thesis by using the fuzzy logic. The method used in this research was the intelligent system method which was called the fuzzy logic. The reason why the fuzzy logic was used was that the fuzzy logic could tolerate the uncertain values. Moreover, the fuzzy logic was based on the reasoning which used the approach to the uncertainty which combined the numeric variable, the linguistic variable, and rule. KEY WORDS: Concentrations, Interests, Motivation, Courses Scores, Fuzzy